Association of IL12B promoter polymorphism with severity of atopic and non-atopic asthma in children - Morahan, G.; Huang, D.; Wu, M.; Holt, B.; White, G.; Kendall, Garth; Sly, Peter; Holt, P. (Elsevier, 2002)
Background Severe asthma is a frequent cause of hospital admission, especially among children. The main environmental triggers of airway inflammation in asthma are viruses and aeroallergens. These agents elicit reciprocal immune responses, characterised by production of T helper 1 and T helper 2 cytokines, respectively. There is no genetic explanation for how hyper-responsiveness to these disparate environmental stimuli develops among individuals with asthma. Our aim was to assess relation between an IL12B promoter polymorphism and asthma.